COMPARATIVE STUDY OF PHRASEOLOGICAL UNITS VERBALIZING THE CONCEPT OF "WEDDING" IN THE ENGLISH AND UZBEK LANGUAGES - Kuchkarova, Zulfizar (Журнал иностранных языков и лингвистики, 2021)
This article is devoted to the comparative analysis of the phraseological units that verbalize the concept of "wedding" in English and Uzbek, which explores the similarities and differences of phraseological units in both languages, reveals the factors that require them.